Corporate Social Responsibility Programs In Industrial Companies Construction (Case Study of PT Brantas Abipraya Bener Purworejo Dam Construction) - Faulta, Vein Sendy (Universitas Dehasen Bengkulu, 2025)
This research evaluates the implementation of Corporate Social Responsibility (CSR) by PT Brantas Abipraya (Persero) in the Bener Dam project, especially in Packages 1 and 4. CSR is implemented through the Social and Environmental Responsibility (CSR) program to support the Sustainable Development Goals (SDGs) and build relationships with surrounding communities. The research method uses a descriptive qualitative approach based on field observations and analysis of company documents. The results show that CSR is active in the fields of education, social, and environment, and is in accordance with regulations. Despite the positive impact, there is a need to increase data transparency, community involvement, and expand the scope of the program so that the benefits are more sustainable.